Prevalence and Health-Adjusted Life Expectancy Among Older Adults With Hypertension in Chinese Rural Areas - Hu, Ze; Liu, Xiaotian; Liao, Wei; Kang, Ning; Ma, Lixia; Mao, Zhenxing; Hou, Jian; Huo, Wenqian; Li, Yuqian; Wang, Chongjian (Frontiers in Public Health, 2022)
Background: The objectives of the present study were to explore the epidemiological characteristics of hypertension among rural older adults in resource-limited regions, and then evaluate the loss of health adjusted life expectancy due to hypertension. Methods: Participants aged from 60 to 79 were enrolled from Henan rural cohort study. The prevalence, awareness, treatment and control of hypertension were detailed across subgroups. Variances within subgroups were identified via Student’s t tests or one-way ANOVA for continuous variables and chi-squared tests for categorical ones, and logistic regression model was employed to detect the potential influencing factors. The health adjusted life expectancy was calculated by the Sullivan method with EuroqOL-5D data. Results: Among 16785 participants, 7472 (44.52%) were attacked by hypertension, 4858 (65.02%) had been already aware of their condition, 4009 (53.65%) were taking antihypertensive medication for treatment, while only 1478 (19.78%) had their hypertension controlled. The prevalence of hypertension was significantly higher among women than men, and increased with age for both genders. For the older ones aged 60 years, the life expectancy was 22.0872 years, and the health adjusted life expectancy was 15.5578 and 15.9418 for those with or without hypertension, respectively. Namely, in this particular age group, subjects without hypertension could gain 0.3840 years of health adjusted life expectancy. Conclusion: The prevalence of hypertension was relatively high while the awareness, treatment and control of that were fairly low. The health adjusted life expectancy of older adults in resource-limited areas could increase from the reduction of hypertension. Strategies pertaining the prevention and treatment of hypertension are needed badly.